GROWTH AND ENDOCRINE FUNCTION IN TUNISIAN THALASSEMIA MAJOR PATIENTS - Naouel GUIRAT (Mediterranean Journal of Hematology and Infectious Diseases)
Beta-thalassemia major (TM) is among prevalent hereditary disorders imposing high expenses on health-care system worldwide. The patient’s survival is dependent on lifetime blood transfusion which leads to iron overload and its toxicity on various organs including endocrine glands. This article provides an overview of  endocrine disorders in beta-TM patients. This single center investigation enrolled 28 beta-TM patients (16 males, 12 females)  regularly transfused with packed red cell since early years of life. For each patient were determined: age, sex, number of transfusions received, history of splenectomy and anthropometric parameters. Evaluation for hormonal status including growth, gonadal, thyroid, adrenal cortex, and parathyroid glands was done for all patients. Dual energy X-ray absorptiometry was used to diagnose osteoporosis. Assessment of iron overload status was performed by measuring the serum ferritin concentration and the results of magnetic resonance imaging T2*. Growth retardation was found in 16 of the 28 studied patients (57 %).Thirteen among them had delayed puberty. Spontaneous puberty was achieved in 16 cases. Growth hormone (GH) deficiency was found in 10 cases (35 %). Seventeen among the studied patients (60 %) developed disorders of glucose homeostasis. Subclinical hypothyroidism was found in six patients (21 %). Intensive chelation therapy had allowed the reversibility of this complication in five cases. Adrenal Insufficiency was found in 9 cases (32%). Hypoparathyroidism has occurred in one case. Ten of the 28 studied patients had osteoporosis (35%). Twenty-three of the 28 studied patients (82%) had at least one endocrine complication.